Using differential transform method to solve fractional non-linear integro-differential equations - L. Noor Ali Hussein (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper we'll to solve the fractional integro-differential equations by employment differential transform method and compare with integro-differential equations by graph.